Evaluation of non-infectious complications of peritoneal dialysis in children: a multicenter study - Aksoy, Gulsah Kaya; Ekim, Mesiha; Bakkaloglu, Sevcan A.; Coskun, Seda; Delibas, Ali; Conkar, Secil; Dusunsel, Ruhan (Springer, 2021)
Background Peritoneal dialysis (PD) is the most common kidney replacement therapy in children. Complications associated with PD affect treatment success and sustainability. The aim of this study was to investigate the frequency of PD-related noninfectious complications and the predisposing factors. Methods Retrospective data from 11 centers in Turkey between 1998 and 2018 was collected. Non-infectious complications of peritoneal dialysis (NICPD), except metabolic ones, in pediatric patients with regular follow-up of at least 3 months were evaluated. Results A total of 275 patients were included. The median age at onset of PD and median duration of PD were 9.1 (IQR, 2.5-13.2) and 7.6 (IQR, 2.8-11.9) years, respectively. A total of 159 (57.8%) patients encountered 302 NICPD within the observation period of 862 patient-years. The most common NIPCD was catheter dysfunction (n = 71, 23.5%). At least one catheter revision was performed in 77 patients (28.0%). Longer PD duration and presence of swan neck tunnel were associated with the development of NICPD (OR 1.191; 95% CI 1.079-1.315, p = 0.001 and OR 1.580; 95% CI 0.660-0.883, p = 0.048, respectively). Peritoneal dialysis was discontinued in 145 patients; 46 of whom (16.7%) switched to hemodialysis. The frequency of patients who were transferred to hemodialysis due to NICPD was 15.2%. Conclusions Peritoneal dialysis-related non-infectious complications may lead to discontinuation of therapy. Presence of swan neck tunnel and long duration of PD increased the rate of NICPD. Careful monitoring of patients is necessary to ensure that PD treatment can be maintained safely.
Keywords: Peritoneal dialysis; Non-infectious complications; Children